COMBATING DRUG ABUSE IN INDIA - Sushil Kumar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This research article focuses on the pressing issue of combating drug abuse in India. The abstract provides a concise overview of the article's key aspects. The abstract begins by highlighting the significance of the problem, emphasizing the urgent need for effective measures to address drug abuse. It outlines the objectives of the research, which include analyzing the current state of drug abuse, exploring its consequences, evaluating existing policies and programs, and promoting awareness and support services. The abstract mentions that the research involves a comprehensive analysis of data, including the prevalence, patterns, and demographics of drug abuse in India. It also investigates the social, economic, and health implications of drug abuse on individuals, families, and communities. Furthermore, it evaluates the effectiveness of existing policies and programs, identifying areas for improvement. The abstract concludes by emphasizing the importance of raising awareness, reducing stigma, and promoting preventive measures and rehabilitation services to combat drug abuse in India. Ultimately, the research aims to contribute to a society where individuals struggling with drug abuse can receive the necessary support and resources to lead healthier and more fulfilling lives.